Analisis Faktor Determinan Kinerja Keuangan UMKM Binaan Desa Giri - Rochmah, Nur; Hudiwinarsih, Gunasti; Mustafida, Nurul (Universitas Muhammadiyah Gresik, 2023)
This study aims to determine the effect of financial literacy, financial management, use of e-commerce and access to capital on the financial performance of MSMEs assisted by Balai Desa Giri. The population in this study were Giri SMEs registered at the Giri Village Hall Development. The sample in this study were 117 UKM assisted by the Giri Village Hall. The data collection carried out in this study was by distributing questionnaires through gforms and questionnaires to respondents. The test equipment carried out in this study used SmartPLS4.0. The results of this study indicate that literacy has no effect on financial performance, financial management has a positive and significant effect on financial performance, the use of e-commerce has no effect on financial performance, and access to capital has a negative and significant effect. on financial performance. Keyword: Financial Literacy; Financial Management; E-Commerce utilization; Access to Capital; Financial Performance; Small and Medium-sized Enterprises (SMEs).